Muslim consumers’ online purchase intention towards Islamic fashion products: A clothing market case - Win, Hla Theingi; Jan, Muhammad Tahir (Amity Directorate of Management and Allied Areas (ADMAA), 2016)
Online shopping has grown exponentially due to the technological growth. This development can be seen in all the developed and developing economies irrespective of the demographic features. This paper seeks to explore the influencing factors of Muslim consumers’ online purchase intention towards Islamic fashion products such as apparel, accssories and hijabs. The study highlights on the better understanding of Muslim consumers’ online shopping intention by focusing on the trend of Islamic fashion products. It also presents the conceptual study of Muslim consumers’ online purchase intention as the main construct based on the past studies and literature findings. Islamic fashion products’ market has a significant growth with its high demand by Muslim consumers from different parts of the world, and thus, fashion designers, manufacturers, retailers and fashion online stores preferably have more opportunities in the emerging fashion market. A conceptual model is proposed to explain online purchase intention and thus, it assists in the understanding of the underlying concept of online shopping and purchase intention. Recommendations and suggestions for further research are also provided to embark on empirical investigation of the present conceptual model.